ANALYZE THE USE OF PROGRESSIVE VERB ON SPONGEBOB MOVIES SERIES - Zhidqi, Elvan Adam; Indriani, Lilia (Universitas Ahmad Dahlan, 2021)
Progressive verb or continuous tense is a verb tense that uses to describe an action or activity that still ongoing. This progressive verb can be in past, present, and future tense. This article inspects progressive verbs in SpongeBob SquarePants Movie Series. Descriptive qualitative is the method of this article. It analyzes the distribution of progressive verb on the movie series, and which one from the progressive verb form that most distribution in movie series.